GROWTH PROFILE OF CYCLOTELLA STRIATA TBI DIATOMS WITH THE ADDITION OF ARTIFICIAL CONTAMINANT NICKEL(II) IONS IN CULTURE MEDIA - Dwiananda Putri, Rizkya
Nickel ion (nickel(II)) pollution in waters has significantly increased due to industrial activities and this condition is toxic to humans and the environment. However, in certain concentrations, nickel(II) ions can actually be essential as a source of micronutrients for the growth of some biota, such as microalgae. Cyclotella striata (C. striata) strain TBI is among the most abundant diatoms in Indonesian waters. However, its growth studies in the presence of high nickel(II) ion content has not been carried out. Therefore, we aim to study the growth profile of the diatom C. striata TBI and its potency to reduce nickel(II) ion levels in the culture media. The study is initiated by analyzing the growth pattern of C. striata using the cell counting method and the optical density method (OD676) in various culture media containing nickel(II) ion contaminants ranging from 0 – 4 mg/L. Then, morphological observations of C. striata were carried out using a light microscope. Afterwards, an analysis of the physical characteristics of the culture media was conducted by measuring the Potential of Hydrogen (pH) and Dissolved Oxygen (DO), as well as analysis of the levels of Ni(II) ions in the culture media using an Atomic Absorption Spectrophotometry (AAS) instrument. This study showed that the growth of C. striata decreased by approximately 9.44 – 50.61% (exponential and stationary phase) in the media containing 2.00 mg/L of nickel(II) ions and the growth was severely inhibited in the media with a nickel(II) ion level of 4.00 mg/L. Morphological observations of C. striata showed cell deformations in the presence of nickel(II) ions. The levels of nickel(II) ions in the culture media compared to blank media did not different significantly (? = 0.05; p-value = 0.6170 and 0.2615>0.05; nickel(II) ions 2.00 and 4.00 mg/L, respectively) until the final day of cultivation. On the other hand, the pH value in the culture media increased until the end of cultivation, while the DO value was decreased. These results showed that the growth of C. striata cells was inhibited by the presence of nickel(II) ions and the greatest inhibition was observed in the media containing 4.00 mg/L of nickel(II) ion.